The maize crop technology characterized by its main indicators at the country level and in Călăraşi country - Georgiana Crudu; Mohamed Dhary Yousif El-Jubouri; Raluca Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The aim of this paper was to analyze the maize crop at the country and the Cæalæaraðsi county level and in the two companies submitted to the case study. This analysis highlighted the importance of themaize crop, crop that is being cultivated on large areas of the country and county, and that also occupies a larger area of the total area of the two companies. The maize crop is very popular in our country because it finds good environmental factors conducive to a proper development, yields per hectare are very good if the technology requirements are complied The indicators used have emphasized the evolution of this culture during the analyzed periods and its capitalization in the companies studied.
Keywords: 330; average production; gross margin; maize; revenues; selling price